Zambujal (Torres Vedras), Portugal - Kunst, Michael (e-Forschungsberichte des DAI, 2023)
In 2012, a small excavation was carried out at the Copper Age fortified settlement of Zambujal. At first the aim was to check some uncertainties that appeared during the preparation of a monograph on the site. But an interesting topographic detail occurred – a certain small ground depression in front of the eastern edge of the walls – which today is filled by eroded sediments. In 2013, a topographic campaign took place, initially to record a map of the northern access road to the site as preliminary work for a planned interpretation centre. On the first day extensive work on land on top of the hill with catterpillars was observed, east of the Copper Age fortifications. Due to the good will of the landowner we could organize geomagnetic prospections which revealed huge systems of ditches, some of which are up to 17 m wide and could possibly have housed the previously unknown Copper Age necropolis.